Factors Affecting the Online Shoppers' Satisfaction: A Study of Indian Online Customers - Sumanjeet, Sumanjeet (The South East Asian Journal of Management, 2008)
The growth of E-Commerce as a business technology has been phenomenal. The Internet and its enabled technologies are just few years old and is already being viewed as the world's most revolutionary development. It has created a universal platform for buying and selling goods and services and driving important business process inside the organization. Small and large companies are using the Internet to make their product information, ordering, and customer support immediately available to help buyers and sellers to make contact. Not only organizations, but customers are also finding some of the greatest of this computer technology come from the E-Commerce application that significantly lower purchase transaction costs by eliminating middlemen in the distribution channels, saves time and energy, wider choices and price comparison. The growing use of Internet and online banking facilities in India provides a developing prospect for the e-marketers. If the marketers know the factors affecting online buyers' behavior and buying habits, then they can further develop their marketing strategies to convert potential customers into active ones, while retaining the existent online customers. Therefore, it is very important for the e-marketers to find out what factors make the customers satisfied and what makes them unsatisfied. This paper empirically examines a survey of 200 customers located in Delhi, Haryana, and Noida. The study examines the factors affecting satisfaction level of online customers. Added to this, the study also try to find out what Indian online customer prefers to buy and what is most preferable mode of payment.